Exploring the Σ+p interaction by measurements of the correlation function - Johann Haidenbauer (Physics Letters B, 2022)
The spin-dependent components of the fundamental hyperon-nucleon interactions are largely unknown. We show that under reasonable assumptions, a measurement of the Σ+p correlation function in high-energy proton-proton or heavy-ion collisions combined with cross section data allows to separate the singlet and the triplet S-wave contributions.